The use of poison pills by US firms over the period 1997-2015: what has been their impact on shareholder value? - Ferraz, D. P.; Lopes, I. T.; Hitzelberger, S. (International Journal of Business Excellence, 2019)
Poison pills are controversial devices for which no common conclusion as to how the market reacts to their adoption exists. This research collates 4,479 poison pill adoption events by American companies over the period 1997-2015. Statistically significant insights and positive abnormal returns were found on the day the poison pill was adopted. It is for this reason that we argue in favour of the shareholder wealth-maximization hypothesis, stating that poison pills protect shareholders by providing management a superior bargaining position. Shareholders react positively to poison pill adoption, particularly if a hostile takeover attempt is anticipated. Furthermore, shareholders seem to value the protective effect of the device, which both provides management a superior bargaining position and allows the maximal possible bid premium to be negotiated.